2006
DOI: 10.1007/s00464-006-9022-x
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes analysis of laparoscopic resection of pancreatic neoplasms

Abstract: Laparoscopic pancreatic resection is safe and feasible in selected patients with pancreatic neoplasms. With a pancreatic duct leak rate of 27%, this problem remains an area of development for the minimally invasive technique.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

7
81
0
4

Year Published

2008
2008
2017
2017

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 96 publications
(92 citation statements)
references
References 29 publications
7
81
0
4
Order By: Relevance
“…To date, most reports of laparoscopic distal pancreatectomy are small series from single institutions. [33][34][35][36][37][38] The occurrence of pancreatic fistula following laparoscopic distal pancreatectomy in these studies has been reported as ranging from 13-50%. 39 In our series, laparoscopic distal pancreatectomy was attempted in 16 patients and completed in 13 patients.…”
Section: Discussionmentioning
confidence: 99%
“…To date, most reports of laparoscopic distal pancreatectomy are small series from single institutions. [33][34][35][36][37][38] The occurrence of pancreatic fistula following laparoscopic distal pancreatectomy in these studies has been reported as ranging from 13-50%. 39 In our series, laparoscopic distal pancreatectomy was attempted in 16 patients and completed in 13 patients.…”
Section: Discussionmentioning
confidence: 99%
“…Rates of pancreatic fistulas range from 16 to 30%, and the rates of those that require intervention range from 7 to 22% [30,31,32,33,34]. If these measures fail, the eventual reoperation rates for LDP are reported to be between 5 and 20% [30,32].…”
Section: Discussionmentioning
confidence: 99%
“…However, the number of publications and published series is small, especially in children [11,12]. This can be explained by the technical difficulty due to the complex location of the organ in the retroperitoneum, its relation to surrounding organs and major vascular structures, and to the precarious pancreatic physiology and the high risk of postoperative complications, especially pancreatic leak [10,13]. Additionally, many surgeons do not have extensive experience in pancreatic and laparoscopic surgery [14,15].…”
Section: Discussionmentioning
confidence: 99%
“…The main problems after surgery of the pancreas are pancreatic fistula, sterile collection, abscess and wound disruption, all of them believed to be due to pancreatic leakage from the stump and reaching an incidence rate of 11-27% [4,7,8,13,15,20,23]. Stapler transection of the pancreas body is the most preferred in laparoscopic pancreatic surgery [5,6,9,13,24,25].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation